An unknown plan for the Casona de San Marcos and (the) Cristóbal de Vargas works (XVIII Century). The b-a-b' module facing its rehabilitation - Mattos-Cárdenas, Leonardo (2016)
The article analyses and reproduces an unknown drawing of the former Jesuit Novitiate of San Antonio Abad in Lima, that nowadays houses the so-called ‘Casona’ of San Marcos University, as well as the Civic Pantheon of the National Independence Grandees (‘Panteón de los Próceres’). Within this ground-plot there is a sector planned to be eventually built and other area -already existing at that period- which testimonies a past unknown till the present. The work and activities of its author, Cristóbal de Vargas -before and after the 1746 earthquake- are described. Finally, three architectural examples in Lima are compared, where the ‘b-a-b module’ was applied in the intercolumns, facing modern criteria on conservation.